Effect of welding on the tensile behavior of high strength steel T-stub joints - Part 2: Numerical study - Chen, C. (2016)
This paper numerically investigated the impact of welding with large heat input on the sensile strength of high strength steel S690 T-stub joints. Finite element simulation was employed to simulate the two-pass thermal-mechanical welding process. Focus was given to the deterioration of mechanical properties in the heat affected zone and its effect on the tensile performance of the whole joint. The simulation results in terms of load-displacement curves are compared with the test results of the high strength steel S690 T-stub joints stated in part I of this twin paper. It is found that the mechanical property deterioration in the heat affected zone of high strength steel caused by welding is remarkably harmful to the global tensile performance of the studied T-stub joints.